Transition‐Metal‐Free Direct Trifluoromethylation and Perfluoroalkylation of Imidazopyridines under Mild Conditions. Issue 7 (12th February 2019) - Han, Shuaijun; Gao, Xianying; Wu, Qingsong; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract: The first transition‐metal‐free method for direct C−H trifluoromethylation of imidazo[1, 2‐a]pyridine derivatives with readily available Ruppert‐Prakash reagent TMSCF3 under mild conditions was described. Moreover, this method could be applied to direct C−H perfluoroalkylation of imidazopyridines, affording a series of novel perfluoroalkylated products in moderate to good yields. Notable advantages of this protocol include easy operation, high‐efficiency and wide substrate scope. Abstract :